Social Media Recruitment How to Successfully Integrate Social Media into Recruitment Strategy - Headworth, Andy (Kogan Page, 2015)
In order to attract the right people into your organization despite a global shortfall of talented candidates, new methods are now needed to reach future talent. Social media needs to become a vital part of any recruitment strategy. Social Media Recruitment combines practical guidance with case studies and insights from industry thought leaders to provide a full understanding of what social media means for HR and recruitment and how to successfully integrate and use it. It covers the essentials from the beginning to the end of the process, including employer branding, interviewing and onboarding, and how to assess the ROI of the social media recruitment strategy.Ideal for all HR and recruitment professionals, and anyone responsible for talent strategy, this practical guide focuses on devising and implementing a social media recruitment strategy that works for your organization and is aligned with your recruitment objectives